Indonesian Junior High School Students’ Science Anxiety Levels: A Cross-Sectional Study of Gender and Grade (Journal of Science Learning, 2026)
Science anxiety is a multidimensional construct that can be influenced by both personal and environmental factors. Junior high school students are in a stage of adolescents, particularly vulnerable to mental health challenges, including anxiety. This research aims to investigate Junior High School students’ science anxiety levels differ by gender and grade level. The researcher carried out survey research by using the SAS instrument with a 5-point Likert scale. The questionnaire comprises 28 questions divided into 2 dimensions, along with 2 open-ended questions. The survey was distributed to 1041 junior high school students, consisting of 583 females and 458 males from grades 7, 8, and 9 across various provinces in Indonesia. The collected data were analyzed with descriptive statistics, then supported by the answers to open-ended questions from the students. The findings show that the average score of science anxiety is 2.66, indicating a moderate level. Regarding gender, there are no significant differences, however the average score of females is higher than males. Regarding grade, there is a significant difference between grade 8 and grade 7, with the highest average score being grade 7. The results showed that the science anxiety levels in junior high school students in a moderate level, so teachers are expected to implement supportive and engaging teaching strategies that can help reduce anxiety and foster a more positive learning environment.